Personal data ordering in context: The interaction of meso-level data governance regimes with macro frameworks - Balázs Bodó; Kristina Irion; Heleen Janssen; Alexandra Giannopoulou (Internet Policy Review, 2021)
The technological infrastructures enabling the collection, processing, and trading of data have fuelled a rapid innovation of data governance models. We differentiate between macro, meso, and micro level models, which correspond to major political blocks; societal-, industry-, or community level systems, and individual approaches, respectively. We focus on meso-level models, which coalesce around: (1) organisations prioritising their own interests over interests of other stakeholders; (2) organisations offering technological and legal tools aiming to empower individuals; (3) community-based data intermediaries fostering collective rights and interests. In this article we assess these meso-level models, and discuss their interaction with the macro-level legal frameworks that have evolved in the US, the EU, and China. The legal landscape has largely remained inconsistent and fragmented, with enforcement struggling to keep up with the latest developments. We argue, first, that the success of meso-logics is largely defined by global economic competition, and, second, that these meso-logics may potentially put the EU's macro-level framework with its mixed internal market and fundamental rights-oriented model under pressure. We conclude that, given the relative absence of a strong macro level-framework and an intensive competition of governance models at meso-level, it may be challenging to avoid compromises to the European macro framework.
Keywords: 300; Data governance; Data ordering; GDPR; Data intermediaries; Data sovereignty